Dlaczego warto pamiętać o mikrobiomie układu oddechowego u pacjentów oddziałów intensywnej terapii? - Siwicka-Gieroba, Dorota; Barud, Malgorzata; Dąbrowski, Wojciech (Anestezjologia Intensywna Terapia, 2021)
In recent years commensal microorganisms are not just “passive occupants”, but important element of homeostasis. There are numerous reports documenting the composition and role of the gut, skin or vagina microbiome but the role of commensal organisms living in the lungs is relatively unknown. Pulmonary microbiome impact on the immune response of the host organism and may indicate new therapeutic directions. Lung microbiome, by modulating the expression of innate immunity genes, causes an increase in the concentration of interleukin (IL)-5, IL-10, interferon γ and C-C motif chemokine ligand 11, affects the toll-like receptor-4-dependent response of pulmonary macrophages and modulate the production of antibacterial peptides contained in the mucus. It is documented that disorders of the lung microbiome contribute to asthma or chronic obstructive pulmonary disease. However it is known that pulmonary dysbiosis also occurs in critically ill patients. It is possible, therefore, that microbiota-targeted therapy may constitute the future therapeutic direction in ICU.